2017
DOI: 10.3310/hta21340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness and cost-effectiveness of lightweight fibreglass heel casts in the management of ulcers of the heel in diabetes: a randomised controlled trial

Abstract: Background Ulcers of the foot in people with diabetes mellitus are slow to heal and result in considerable cost and patient suffering. The prognosis is worst for ulcers of the heel. Objective To assess both the clinical effectiveness and the cost-effectiveness of lightweight fibreglass casts in the management of heel ulcers. Design A pragmatic, multicentre, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(72 citation statements)
references
References 19 publications
1
71
0
Order By: Relevance
“…We identified one large RCT with very low risk of bias . This RCT randomised 509 patients, most (72%) with a non‐plantar rearfoot DFU, to receive either a custom‐made, lightweight, fibreglass heel cast with usual care or usual care alone .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified one large RCT with very low risk of bias . This RCT randomised 509 patients, most (72%) with a non‐plantar rearfoot DFU, to receive either a custom‐made, lightweight, fibreglass heel cast with usual care or usual care alone .…”
Section: Resultsmentioning
confidence: 99%
“…A validation set of 30 publications was created, including key studies known to the authors published since our previous search (July 29, 2014) . Using this set, the search strings used were validated; ie, each publication had to be identified before the search strings were used in this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…The study found no differences in ulcer healing, adverse events, or patient preferences but did find the heel cast had higher overall costs . Although patients with nonplantar DFU made up the majority of included patients, the RCT did not report outcomes specifically for the nonplantar DFU …”
Section: Recommendationsmentioning
confidence: 95%
“…This low‐quality RCT reported that those ulcers offloaded with a TCC had shorter time‐to‐healing than those using therapeutic footwear (69 vs 107 d), but no statistical significance was reported . Another high‐quality RCT compared a custom‐made fibreglass heel cast with standard wound care in patients with heel ulcers, but of which most (72%) were nonplantar . The authors did not specifically report on plantar heel ulcers.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation